RELEVANSI ANTARA PENILAIAN DAN PENGUKURAN DARI LABA AKUNTANSI KONVENSIONAL UNTUK AKUNTANSI SYARIAH - Akhmad Hulaify (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This is a library-comparative research of the profit mechanism assessment and measurement of two calculation methods, which is between conventional models and sharia models. The approaches used in this study consists of four; normative approach, sociological approach, historical approach; and philosophical approach. The four approaches used with the aim to reveal the method of calculating profits with the Islamic accounting system. The data obtained from the literature is then processed by making reductions and classifications to draw the relationships pattern between the data found and the core problem of this study. The processed data is then analyzed to find answers to the problems of this research.This research finds that there are significant differences where the sharia system has more benefits. In Islamic accounting, the calculation model can encourage the economic growth of the people. Thus the element of sharia is clearly able to bring goodness and salvation (maslahah) in the life of mankind.The results of this study are intended to provide public knowledge and understanding of the sharia method which not only brings worldly benefits but also avoids the harm that affects the lives of the world and the hereafter. This understanding is a means to realize happiness of life (al-falah) in the world and the hereafter. Keywords:Relevance, Assessment, Measurement, Conventional, Accounting,Sharia.